2022
DOI: 10.3390/ijms23168937
|View full text |Cite
|
Sign up to set email alerts
|

Differential CFTR-Interactome Proximity Labeling Procedures Identify Enrichment in Multiple SLC Transporters

Abstract: Proteins interacting with CFTR and its mutants have been intensively studied using different experimental approaches. These studies provided information on the cellular processes leading to proper protein folding, routing to the plasma membrane, recycling, activation and degradation. Recently, new approaches have been developed based on the proximity labeling of protein partners or proteins in close vicinity and their subsequent identification by mass spectrometry. In this study, we evaluated TurboID- and APEX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…The interactome of WT, F508del and N1303K-CFTR was assessed in HEK293 cells using the TurboID proximity labeling approach, as previously described (32).…”
Section: Cftr Interactomementioning
confidence: 99%
“…The interactome of WT, F508del and N1303K-CFTR was assessed in HEK293 cells using the TurboID proximity labeling approach, as previously described (32).…”
Section: Cftr Interactomementioning
confidence: 99%
“…Many studies simply enrich over endogenous biotinylation and bead background. [59][60][61][62] Other studies expressed forms of TurboID alone that were localized to the specific cellular compartment that the protein of interest resided, such as the cellular membrane. 48,49,51,52 As a non-TurboID-expressing wild-type control with a similar genetic background, we used a fly strain in which endogenous kdm5 is removed and HA-tagged KDM5 is expressed using its endogenous promoter from a transgene inserted at the same locus as the TurboID constructs (kdm5 140 ;gkdm5 WT ).…”
Section: Determining the Proper Controls To Identify The Kdm5 Proximi...mentioning
confidence: 99%
“…This is important not only in an etiopathological perspective but also in terms of the variable individual response to corrector therapy, upon which restoring CFTR expression and function should occur in harmony with co-expressed ion channels to preserve tissue physiology. In this regard, recent interactome studies aimed at identifying CFTR protein partners have revealed a multiplicity of proteins [ 8 ], including multiple solute carrier (SLC) transporters [ 9 ], suggesting that ion channels are not only reciprocally influenced by ions movement but also by direct, physical interactions, the quantitative characterization of which [ 10 ] may inform on the extent of regulation of CFTR function by single protein–protein interactions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%